2021
DOI: 10.1093/neuros/nyab316
|View full text |Cite
|
Sign up to set email alerts
|

Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines for Perioperative Spine: Preoperative Surgical Risk Assessment

Abstract: BACKGROUND Patient factors (increased body mass index [BMI], smoking, and diabetes) may impact outcomes after spine surgery. There is a lack of consensus regarding which factors should be screened for and potentially modified preoperatively to optimize outcome. OBJECTIVE The purpose of this evidence-based clinical practice guideline is to determine if preoperative patient factors of diabetes, smoking, and increased BMI impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Lim et al ( 20 ) analyzed 4,778 patients and showed that patients with preoperative hemoglobin A1c (HbA1c) > 8% were more likely to experience postoperative complication; indeed, in our study, glycosylated hemoglobin ≥6.5% was an independent risk factor affecting the satisfaction of OTCF patients, indicating that controlling HbA1C level <6.5% was beneficial. What's more, a systematic review showed that preoperativeHbA1c > 7.5 mg/dl was associated with an increased risk of reoperation or infection after spine surgery ( 21 ). Therefore, it is important for diabetic patients to maintain good HbA1C control to prevent the development of complications and improve patient satisfaction, especially HbA1C level more than 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al ( 20 ) analyzed 4,778 patients and showed that patients with preoperative hemoglobin A1c (HbA1c) > 8% were more likely to experience postoperative complication; indeed, in our study, glycosylated hemoglobin ≥6.5% was an independent risk factor affecting the satisfaction of OTCF patients, indicating that controlling HbA1C level <6.5% was beneficial. What's more, a systematic review showed that preoperativeHbA1c > 7.5 mg/dl was associated with an increased risk of reoperation or infection after spine surgery ( 21 ). Therefore, it is important for diabetic patients to maintain good HbA1C control to prevent the development of complications and improve patient satisfaction, especially HbA1C level more than 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] All patients who smoked preoperatively were counseled extensively regarding the increased risks of complications according to evidence-based guidelines. 31 In a systematic review of decompression alone in the setting of DLS, other risk factors for additional surgery included preoperative severe lumbar coronal Cobb angle (mean 29.6°), increased preoperative PT (mean 28.3°), preoperative PI-LL (mean 35.5°), and poor facet preservation (approximately 50%) on the approach side of the concavity. 24 In another systematic review of prognostic factors for curve progression in untreated DLS, Faraj et al found that the majority of prognostic factors were limited, conflicting, or inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…These additional findings were expected and supported by the literature. Harrop et al 25 performed a systematic literature review to determine whether patient factors of diabetes, smoking, and increased BMI affect surgical outcomes such as postoperative infection. The authors concluded that there is conflicting evidence associating elevated BMI with SSI in patients undergoing spinal surgery.…”
Section: Discussionmentioning
confidence: 99%